A prospective comparative study of Proximal Femoral Nailing Anti-rotation (PFNA) and Sliding Hip Screw (SHS) for Per-trochanteric Femur Fracture - Amer Khan, Muhammad Ali , Ayesha Tahir , Muhammad Saleem , Usman Sarwar , Imran Manzoor, Amer Khan, Muhammad Ali , Ayesha Tahir , Muhammad Saleem , Usman Sarwar , Imran Manzoor (Journal of Rawalpindi Medical College, 2020)
Objectives: To determine the functional outcome, operative risks, rate of union, and complication in Per-trochanteric Fracture fixed with PFNA and SHS. Material and Methods: The present study has been conducted at Shalamar Medical and Dental College Lahore from January 2018 to December 2018.40 patients with per-trochanteric femur fracture treated with proximal femoral nailing anti-rotation (PFNA) and Sliding hip screw (SHS) were enrolled in our study.20 patients were treated by PFNA and 20 patients by SHS. Timing of surgery, mobilization status, hospital stay, infection, weight-bearing status, radiological union, complications both technical and implant-related, amount of blood loss(ml), C ARM Exposures, and Harris hip score at the end of 6 months were recorded. Results: Union was better in the PFNA group (95%) as compared to the SHS group (85%). Complication rate, hospital stay, surgery timing, and requirement of revision surgery were more in the SHS group. The functional outcome was better in the PFNA group as compared to the SHS group. Conclusion: From our study, we concluded that PFNA is a better alternative than SHS in terms of higher union rates, low complication rates, and better functional outcomes.